IPTA application status - New, Straits Times (NST, 2014)
Sijil Tinggi Persekolahan Malaysia holders for those with its equivalent can check their applications to public institutions of higher learning (IPTAs) on the Unit Pusat Universiti (UPU) website from noon today.